(untitled) (Bangladesh Journal of Botany, 2022)
To know the impacts of climate change on cashew production, the correlation study of different climatic factors and growth and reproductive characters of different released varieties of cashew was conducted. Grafted plants of 24 released cashew varieties developed by different cashew research stations of India were planted at the semi arid regions of West Bengal, India in 2010.Maximum temperature and relative humidity during the pre-flowering stage has strong positive correlation with flowering intensity. Relative humidity is the major factor influencing different reproductive characters of cashew nut. Vengurla-7, Bhaskara, Ullal-3, BPP-8 and Madakkathara-II were found to be suitable for the semi arid climate.The varieties Like Bhaskara, Vengurla-7, VRI-3, BPP-6, Madakkathara-1, Kanaka, Vengurla-1, Vengurla-6, Ulla-3 and UN-50 are the varieties which were found to be more susceptible to yield loss due to less relative humidity (%) and it is better to recommend those varieties for the coastal areas. NRCC-2, Jhargram-1, Vengurla-4, BPP-4, Ullal-4, Madakkathara-2, Bhubaneswar-1, K-22-1, Chintamani-1, Goa-1, BPP-8 and Dhana may be recommended for the places where relative humidity is less during the fruiting period. Bangladesh J. Bot. 51(3): 527-539, 2022 (September)